Niñez apátrida: una consecuencia de la migración en Latinoamérica (2022)
People who, for social, political, economic or violent reasons, find it necessary to leave their country of origin generate massive migration policy problems in the States where they seek asylum. Colombia is a country with innumerable social situations related to the exodus, being one of the countries that, in recent decades, has received the largest flow of citizens belonging to other countries, who for mostly socioeconomic reasons are forced to leave their place of residence. birth. Venezuela is one of the states that has been most affected by the departure of citizens from their country. The precarious economic and social conditions have led its inhabitants to the need to find solutions in neighboring countries like ours. Colombia has had to implement specific actions that are oriented to the care of the Venezuelan population due to the exponential growth of the transfer of inhabitants of this country to the national territory. It should be clarified that, as mentioned by the United Nations High Commissioner for Refugees (UNHCR), it considers that the majority of Venezuelan nationals are in need of international protection under the criteria contained in the Cartagena declaration, based on the threats to his life, security or freedom resulting from events that are currently seriously disturbing public order in Venezuela. Said like this, the diagnosis of the forced and disproportionate migration to which the Venezuelan population is subjected must be taken into account. Where the majority are in a state of need and protection. As a consequence of the unimaginable number of inhabitants arriving daily in the country, legislative phenomena are produced that leave many of those who seek protection in an orphaned condition. Many children born among migrants turn out to be children of no legislation, they are not protected by the government they are fleeing from, but the government they are going to does not accept them either, because they were not born there, they did not show residence, they are called stateless.